Design Komposisi Beton Untuk Panel Beton Menggunakan Bahan Tambah Serat Fiberglass - Andanu, Surya Laksa; Abrar, Aidil; Putra, Sony Adiya; Desriyati, Welly (Sekolah Tinggi Teknologi Dumai, 2024)
To overcome the problem of deficiencies in concrete, there are various ways, one of which is the innovation of mixing concrete with fiber which is an innovation to increase the compressive strength of concrete. Fiber concrete is a composite material in which fiber is added to the concrete mixture. The fiber used in this research is Fiberglass. Comparison results of the compressive strength of normal concrete and Fiberglass fiber. Normal concrete aged 7 days has an average compressive strength of 107.76 Kg/Cm2, aged 14 days the average compressive strength is 154.09 Kg/cm2, aged 28 days the average compressive strength is 166.17 Kg/cm2. And for concrete with added 3% Fiberglass fiber, aged 7 days, the average compressive strength is 117.83 Kg/cm2, aged 14 days, the average compressive strength is 148.05 Kg/cm2, aged 28 days, the average compressive strength is 164, 66 Kg/cm2. for concrete with 5% Fiberglass fiber added at age 7 the average compressive strength is 123.87 Kg/cm2, at 14 days the average compressive strength is 146.53 Kg/cm2, at 28 days the average compressive strength is 187.32 Kg/cm2. for concrete with added 9% Fiberglass fiber, aged 7 days, the average compressive strength is 99.70 Kg/cm2, aged 14 days, the average compressive strength is 128.41 Kg/cm2, aged 28 days, the average compressive strength is 149.56 Kg/cm2.